2019
DOI: 10.1123/japa.2018-0294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eccentric-Focused Versus Conventional Training on Lower Limb Muscular Strength in Older Adults: A Systematic Review With Meta-Analysis

Abstract: Eccentric-focused training promotes greater gains in muscle strength compared with other types of training in adults. However, for older adults, these findings are still not well understood. A systematic review and meta-analysis were performed using manuscripts that performed eccentric-focused and conventional resistance training for at least 4 weeks and evaluated maximum muscle strength through tests of maximum repetitions in weight machine exercises (knee extension and leg press exercises). Five studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“… 21 The large effect size of muscle strength for the eccentric focused training in the pre-training versus post-training comparison was observed. 55 It was also found that eccentric-focused training greatly increased muscle strength and cross-sectional area of the muscle compared to the combination of concentric and isometric training. 55 …”
Section: Resultsmentioning
confidence: 97%
“… 21 The large effect size of muscle strength for the eccentric focused training in the pre-training versus post-training comparison was observed. 55 It was also found that eccentric-focused training greatly increased muscle strength and cross-sectional area of the muscle compared to the combination of concentric and isometric training. 55 …”
Section: Resultsmentioning
confidence: 97%
“…The most recent recommendations from the National Strength and Conditioning Association highlights the importance of eccentric exercise to improve muscle mass, physical function, and power in older individuals with limited tolerability and diminished muscular strength [10,12,13]. Eccentric resistance exercise has gained considerable attention due to its unique properties, such as low energy cost and high muscle force production compared to concentric action [14,15]. However, the acute physiological response to eccentric exercise in sedentary obese older women with a different MQI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, performance of everyday functional tasks such as crossing the road or carrying bags from the store are also, to some extent, associated with isokinetic strength (Doherty, 2003 ). Two very recent systematic reviews focused on the effect of eccentric training in healthy older adults (Molinari et al, 2019 ; Kulkarni et al, 2021 ). Molinari et al ( 2019 ) included 5 studies with muscle strength outcomes, and reported similar effects of eccentric exercises and traditional resistance exercises, with the data slightly favoring the former.…”
Section: Introductionmentioning
confidence: 99%
“…Two very recent systematic reviews focused on the effect of eccentric training in healthy older adults (Molinari et al, 2019 ; Kulkarni et al, 2021 ). Molinari et al ( 2019 ) included 5 studies with muscle strength outcomes, and reported similar effects of eccentric exercises and traditional resistance exercises, with the data slightly favoring the former. Kulkarni et al ( 2021 ) examined 10 studies and reported that eccentric exercises can be as effective as conventional exercises in older adults for improving functional performance.…”
Section: Introductionmentioning
confidence: 99%